Toxic epidermal necrolysis induced by acetaminophen: a case report - Gupta, M. C.; Mittal, Niti; Sharma, Nishikant (International Journal of Basic & Clinical Pharmacology, 2017)
Acetaminophen is a very commonly used analgesic and antipyretic drug across various age groups. Although mild to moderate cutaneous reactions have been reported quite frequently, serious reactions like Stevens –Johnson syndrome and Toxic epidermal necrolysis (TEN) are very rare. We report the case of a 10 year old child who had TEN after ingestion of tablet acetaminophen. This case report highlights the need to be critically aware of this rare and serious adverse effect of this commonly used over the counter drug.